Ternary Blend Solar Cells Based on a Conjugated Polymer With Diketopyrrolopyrrole and Carbazole Units - Wang, Yanbin; Chen, Jinxing; Kim, Hyung Do; Wang, Biaobing; Iriguchi, Ryo; Ohkita, Hideo (Frontiers in Energy Research, 2018)
Herein, we have synthesized a low-bandgap polymer (PCDPP4T) consisting of diketopyrrolopyrrole (DPP) and carbazole (Cz) units in the main chain. The absorption coefficient is as high as 1.3 ×10^5 cm−1 for PCDPP4T, which is slightly higher than 1.0 × 10^5 cm−1 for the monomer model compound (DPP4T-Cz). For ternary blend solar cells based on poly(3-hexylthiophene) (P3HT), [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), and only 3.4 wt% of PCDPP4T, the photocurrent increased and thus the power conversion efficiency (PCE) was improved by 30% compared to those of P3HT/PCBM binary reference cells. The improved photocurrent was ascribed partly to complementary absorption of PCDPP4T in the near-infrared (near-IR) region, and partly to efficient long-range energy transfer from P3HT to PCDPP4T, which can collect P3HT excitons that would be lost in large P3HT domains. We also discuss the origin for the improved photocurrent and requirements for further improvements.